Effects of Processing on the Acceptability of "Frozen" Extraposed Constituents. (16th October 2015) - Hofmeister, Philip; Culicover, Peter; Winkler, Susanne
Abstract: In syntactic theory, "freezing" refers to the idea that a constituent extraposed to a noncanonical position is resistant to extraction of any of its subconstituents ( What did Terry see a movie yesterday about ——— ? ). The unacceptability of such examples, compared to minimally different sentences without extraposition, has been claimed to be a result of a grammatical constraint on dependency formation, such as Ross's (1967) Frozen Structure Constraint. Here, we argue that the gradient pattern of acceptability associated with such examples is better explained in terms of processing complexity. Experimental evidence from a controlled acceptability task shows that the total penalty for extraction from extraposed constituents is predictable from the summed acceptability penalties independently linked to extraction and extraposition. As prior research links both of these displacement phenomena to increased processing costs, we conclude that a grammar of unbounded dependencies in English does not require a "freezing" constraint for the explanation of these cases.